Fabrication of Sb2S3 sensitized TiO2 nanorod array solar cells using spin-coating assisted successive ionic layer absorption and reaction. (June 2019) - Ying, Chao; Shi, Chengwu; Lv, Kai; Ma, Chengfeng; Guo, Fuling; Fu, Haoyu
Abstract: Sb2 S3 was successfully deposited on the TiO2 nanorod arrays with the length of 600 nm, the diameter of 20 nm and the areal density of 520 μm −2 by step-by-step spin-coating the SbCl3 solution in methanol and the Na2 S solution in methanol/water (v/v, 95/5) via successive ionic layer absorption and reaction. Then the Sb2 S3 sensitized TiO2 nanorod arrays were annealed at 300 ℃ for 6 min in an N2 atmosphere. The corresponding solar cells with spiro -OMeTAD achieved the photovoltaic conversion efficiency of 3.76%, along with the open-circuit voltage of 0.55 V, the short-circuit photocurrent density of 11.26 mA⋅ cm- −2 and the fill factor of 0.61.